Transition radiation induced by nonrelativistic electron bunches - Bolotov, V.N.; Kononenko, S.I.; Muratov, V.I.; Fedorchenko, V.D. (Вопросы атомной науки и техники, 2009)
The experiments showed that the Bernstein – Green – Kruskal (BGK)-waves can be used to form short electron bunches with time durations ranging between 50 and 100 ps. Experiments on generating electromagnetic pulses (EMPs) by using nonrelativistic electron bunches passing through diaphragms of various radii and complex geometries are described. Results obtained may also be used in designing devices for generating EMPs with tunable characteristics.